Influence of experimental metabolic syndrome on bioimpedance spectroscopy indicators of rat body - Ivanenko, T.; Hrekova, T.; Abramova, T.; Shiryaeva, A.; Vasilenko, G. (Journal of Education, Health and Sport, 2021)
The objective of this experiment was to establish sex-related differences in the parameters of bioimpedance spectroscopy of the Wistar rat’s bodies in the experimental metabolic syndrome (endocrine-salt model). Sexual dependencies of bioimpedance measurements in intact animals have been determined for the first time: males have higher amount of total fluid, but lower one of total fat. The intra/extracellular fluid balance in males is characterized with ratio 2:1, while in females is the other one - 1:1. For the first time the formation of the metabolic syndrome has already been determined on the seventh day in females which lead to decreasing in the percentage of total fat and to changing of the intra / extracellular fluid balance to ‘male’ type - 2:1. The last one should be considered as a sign of intracellular hyperhydration. In males the examined parameters have been being within the control values ​​throughout 21 days of experiment.